A 350 mV, 280 μW 1.5-to-4.5-GHz wideband folded mixer adopting capacitive-cross-plus-magnetic-coupling - Vitee, Nandini; Ramiah, Harikrishnan; Balan, Zechariah (Elsevier, 2020)
This paper describes a 1.5–4.5 GHz CMOS wideband mixer that operates from a single supply of 350 mV, allowing direct powering from various energy harvesting sources. The key techniques adopted for low power and low voltage operation are: (1) complementary transconductance stage in folded topology and current reuse, (2) forward body bias, and (3) gm-boosting by capacitor-cross and transformer coupled (CCTC). The CCTC achieves a high conversion gain (Gc) and a wideband input impedance matching under low power operation. Designed in 130-nm CMOS process, the mixer exhibits Gc of 12.2–16.4 dB and noise figure (NF) of 8.2–12 dB. The maximum input-referred 3rd-order intercept point (IIP3) is −11 dBm while consuming only 280 μW of power at an intermediate frequency (IF) of 50 MHz. The low power and low supply operation render the proposed CMOS mixer suitable for communication among multiple sensor nodes in a wireless body-area sensor network (WBAN). © 2020